Lewin's Genes XII - Jocelyn E Krebs (Jones & Bartlett Learning, 2018)
Long considered the quintessential molecular biology textbook, for decades Lewin's Genes has provided the most modern presentation to this transformative and dynamic science. Now in its twelfth edition, this classic text continues to lead with new information and cutting-edge developments, covering gene structure, sequencing, organization, and expression. Leading scientists provide revisions and updates in their respective areas of study offering readers current research and relevant information on the rapidly changing subjects in molecular biology. No other text offers a broader understanding of this exciting and vital science or does so with higher quality art and illustrations. Lewin's Genes XII continues to be the clear choice for molecular biology and genetics.